A Comprehensive Review of Islamic Microfinance: A Study for Practitioner and Government - Dede Kurnia; Nandang Nandang; Ismail Yusup (The Future of Education Journal, 2026)
This study examines various literatures related to Islamic microfinance published in accredited international journals, the aim is to find out how far the development of Islamic microfinance issues internationally forward, also provide new insights for practitioner and the government as policy makers. This research was conducted using systematic literature review method to examine critically the information relevant to the issues of Islamic microfinance. The results of the study found that during 2014-2021, Indonesia was the country with the most research on Islamic microfinance issues, meanwhile financial inclusion was also the most dominant topic studied in Islamic microfinance research. The results of the analysis of the Islamic microfinance literature also show that Islamic microfinance institutions need to carry out a proactive strategy to ensure that the provided financial services can improve the social and economic status of the community properly. In addition, the support of government in the regulations and infrastructure is also needed to improve its performance and maintain the sustainability of Islamic microfinance institution itself.